The association of angiotensin-converting enzyme inhibitors and angiotensin 2 receptor blockers with renal protection in patients with SARS-CoV-2. (3rd October 2022) - Douen, A D; Tan, S T; Sukoo-Pertab, M S; Bowser, C B; Busari, O B; Siu, W S; Panetti, P R; Kedarisetti, S K; Romney, W R; Ramdass, R P; Lee, W L; Juang, G J; et al.
Abstract: Background: Kidney dysfunction is a prevalent disease that leads to many complications over time, such as hypertension, heart disease, and death. ACEI/ARBs are known to be renoprotective. However, few studies describe the association between ACEI/ARB use and kidney dysfunction in patients with SARS-CoV-2 infection. Purpose: To explore the association between patients with SARS-CoV-2 and kidney dysfunction in patients taking an ACEI/ARB. We hypothesize a negative association between patients with SARS-CoV-2 taking an ACEI/ARB and kidney dysfunction. Methods: A retrospective query between March 2020 and April 2021 was performed in patients 18 years and older who tested positive for SARS-CoV-2 using a polymerase chain reaction test. Patients were divided into two groups: kidney dysfunction and no kidney dysfunction. Kidney dysfunction was defined as any diagnosis of chronic kidney disease or acute kidney injury. Primary outcomes were all-cause mortality and hospitalization rate. Secondary outcomes included myocardial infarction (MI), hypotension, intubation, vasopressor use, ventricular tachycardia, and ventricular fibrillation. We used multivariate logistic regression to adjust for baseline characteristics. Results: We identified 996 patients with kidney dysfunction and 22, 106 without kidney dysfunction who tested positive for SARS-CoV-2. The incidence was 258 (25.9%) for ACEI/ARB use in patients with kidney dysfunction. Adjusted odds ratio (OR) for patients with kidney dysfunction was 5.705 (95% Confidence Interval [CI]: 4.554–7.146; p<0.001) for hospitalization, 0.895 (95% CI: 0.707–1.135; p<0.361) for patients taking ACEI/ARB, and 0.529 (95% CI: 0.333–0.838; <0.007) for mortality in patients with kidney dysfunction who took ACEI/ARB. All secondary outcomes had significantly greater adjusted OR (p<0.001), except for MI (p<0.339), ventricular tachycardia (p<0.697), and ventricular fibrillation (p<0.060). Conclusion: To date, the benefits of ACEI/ARB in SARS-CoV-2 patients have been controversial. While ACEI/ARB is known to have renoprotective properties, we did not find a significant association between ACEI/ARB and kidney dysfunction in patients with SARS-CoV-2. However, we found the use of ACEI/ARB in patients with kidney dysfunction to be associated with lower mortality. Therefore, clinicians should continue using this medication for its mortality benefits in patients with kidney dysfunction and its cardioprotective effects. Funding Acknowledgement: Type of funding sources: None.